2006
DOI: 10.1016/j.dsr2.2006.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community response to Fe and temperature gradients in the NE (SERIES) and NW (SEEDS) subarctic Pacific Ocean

Abstract: Ship-board iron enrichment bottle experiments were carried out with samples collected at the mesoscale iron fertilization experimental site (SERIES) in the subarctic NE Pacific in the summer of 2002. Samples were collected on Day 14 of the experiment outside the patch that was in a typical HNLC (high nitrate and low chlorophyll) condition. The iron concentration in the incubation bottles ranged from 0.1 to 2.0 nM by adding FeCl 3 solution. The increase in Chl-a in the micro (>10 µm) and nano-sized (2-10 µm) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…The rates for large diatoms are often substantially higher than our assumed value (>0.2 nM, Timmermans et al, de Baar et al, 2005) but lower rates have been observed for smaller diatoms from HNLC regions (0.12 nM for the Iron Ex II diatom dominated bloom, Fitzwater et al, 1996; diatom values of 0.05-0.13 nM for the Ross Sea, Coale et al, 2003). Kudo et al (2006) estimated values of 0.10 nM and 0.08 nM for the micro-and nano-sized phytoplankton fractions in the SERIES experiment in the NW subarctic Pacific.…”
Section: Improving the Bec Iron Cycle Parameterizationscontrasting
confidence: 50%
“…The rates for large diatoms are often substantially higher than our assumed value (>0.2 nM, Timmermans et al, de Baar et al, 2005) but lower rates have been observed for smaller diatoms from HNLC regions (0.12 nM for the Iron Ex II diatom dominated bloom, Fitzwater et al, 1996; diatom values of 0.05-0.13 nM for the Ross Sea, Coale et al, 2003). Kudo et al (2006) estimated values of 0.10 nM and 0.08 nM for the micro-and nano-sized phytoplankton fractions in the SERIES experiment in the NW subarctic Pacific.…”
Section: Improving the Bec Iron Cycle Parameterizationscontrasting
confidence: 50%
“…Higher irradiance may stimulate algal photosynthetic activity and could also have an effect on iron availability by enhancing photochemical redox cycles. Although relatively low K s values had been estimated for phytoplankton community during the Subarctic Ecosystem Response to Iron Enrichment Study (SERIES) experiment (Kudo et al 2006), these results suggest that not only the large species, such as diatoms, but also small algal species are substantially limited by iron availability both in western and eastern subarctic North Pacific. Considering the differences in the biological and geochemical characteristics between the Western Subarctic Gyre and the Alaska Gyre Suzuki et al 2002), it is surprising to observe similar K s values in these two gyres, as algal species composition as well as other environmental factors, such as light and availability of other nutrient elements, are likely to influence the iron requirement of the phytoplankton community.…”
Section: -3 Growth Responses Of Natural Assemblage To the Changing mentioning
confidence: 78%
“…Although the K s values (<0.1 nM) reported by Kudo et al (2006) are in ranges similar to those of Antarctic phytoplankton communities (Blain et al 2002;Coale et al 2003), these low values seem to be partly derived from significant growth of nanoand microphytoplankton (0.3 d -1 ) in the control bottles, and such changes in chlorophyll and nutrients in the control bottles would be problematic for the estimation of K s values. Furthermore, their experiments were conducted at 90% of surface irradiance, which is 2-4 times stronger than that at the depth of samplewater collection.…”
Section: -3 Growth Responses Of Natural Assemblage To the Changing mentioning
confidence: 86%
See 1 more Smart Citation
“…Before the experiments, the polycarbonate bottles had been sequentially cleaned by soaking in 5% alkaline detergent (Extran MA1, Millipore) for a day, in 10% HCl for a day, and in Milli-Q water for 2 d. This cleaning process was repeated twice. On the basis of the results of Kudo et al (2006), who carried out Fe-enrichment bottle experiments in the northeast subarctic Pacific, we supplemented two bottles with an acidified ferric chloride (FeCl 3 ) solution to increase the Fe concentration by 2 nmol L 21 . Two bottles without Fe addition were prepared as control experiments.…”
Section: Methodsmentioning
confidence: 99%